2023
DOI: 10.3390/nu15040875
|View full text |Cite|
|
Sign up to set email alerts
|

Feasibility Study of Lactobacillus Plantarum 299v Probiotic Supplementation in an Urban Academic Facility among Diverse Pregnant Individuals

Abstract: (1) Background: Despite iron intake recommendations, over a quarter of pregnant individuals have iron deficiency. Lactobacillus plantarum 299v enhances iron absorption in non-pregnant populations and may have positive effects in pregnancy among those with sufficient iron stores; however, no studies have evaluated the effect of Lp299v on maternal and neonatal iron status among individuals at risk for iron deficiency anemia in pregnancy. Thus, this study aims to assess the feasibility and preliminary efficacy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…In another study, the Lp299v strain increased IL-10 and decreased pro-inflammatory tumor necrosis factor-α (TNF-α) levels [80]. Lp299v can also benefit blood iron levels in women [84,85]. The meta-analysis by Vonderheid et al also showed that the Lp299v strain, among other strains, is very effective in supporting increased iron absorption [86].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, the Lp299v strain increased IL-10 and decreased pro-inflammatory tumor necrosis factor-α (TNF-α) levels [80]. Lp299v can also benefit blood iron levels in women [84,85]. The meta-analysis by Vonderheid et al also showed that the Lp299v strain, among other strains, is very effective in supporting increased iron absorption [86].…”
Section: Discussionmentioning
confidence: 99%
“…There was an error in the original publication. LP299V ® is a registered trademark by Probi AB and this was not indicated in the original publication [1]. A correction has been made to all LP299V ® references throughout the text and tables: "Lp299v" should be replaced with "LP299V ® ".…”
Section: Text Correctionmentioning
confidence: 99%
“…LP supplementation associated with positive outcomes is observed in bowel disease, atopic dermatitis, intestinal infections, and maternal and neonatal hematological issues. LP is one of the most plausible lactic acid bacterium species found in diverse ecological conditions ( Seddik et al, 2017 ; Zhou et al, 2021 ; Jeong et al, 2023 ; OjiNjideka Hemphill et al, 2023 ). LP’s effect on aging is in the initial stage ( Lin et al, 2021 ; Ding et al, 2022 ; Kumar et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%